Does forced whisper have an impact on voice parameters? - Echternach, Matthias; Köberlein, Marie; Döllinger, Michael; Kirsch, Jonas; Pilsl, Theresa (European Archives of Oto-Rhino-Laryngology, 2024)
OBJECTIVES: There has been the assumption that whispering may impact vocal function, leading to the widespread recommendation against its practice after phonosurgery. However, the extent to which whispering affects vocal function and vocal fold oscillation patterns remains unclear. METHODS: 10 vocally healthy subjects (5 male, 5 female) were instructed to forcefully whisper a standardized text for 10 min at a sound level of 70 dB(A), measured at a microphone distance of 30 cm to the mouth. Prior to and following the whisper loading, the dysphonia severity index was assessed. Simultaneously, recordings of high speed videolaryngoscopy (HSV), electroglottography, and audio signals during sustained phonation on the vowel /i/ (250 Hz for females and 125 Hz for males) were analyzed after segmentation of the HSV material. RESULTS: The pre-post analysis revealed only minor changes after the intervention. These changes included a rise in minimum intensity, an increase in the glottal area waveform-derived open quotient, and the glottal gap index. However, no statistically significant changes were observed in the harmonic-to-noise-ratio, the glottal- to-noise-excitation-ratio, and the electroglottographic open quotient. CONCLUSION: Overall, the study suggests that there are only small effects on vocal function in consequence of a forced whisper loading.
EVALuna2:570022